New Fisheries-related data from the Mediterranean Sea (December, 2017) - KAPIRIS, K.; ANASTASOPOULOU, A.; KOUSTENI, V.; LAMPRI, P-N; MINOS, G.; MYTILINEOU, CH.; OIKONOMIDIS, G. (Mediterranean Marine Science, 2018)
In this collective article we discuss the relationships between the otolith measurements (weight, radius) and total length of Mullus surmuletus in the Aegean and Ionian Seas and of Pagellus erythrinus samples caught in the Southern Aegean Sea. In addition to the above mentioned studies, the abundance of the rare fish Echiodon dentatus in the Kyklades and the Saronikos Gulf (Central Greece) is also documented. The first weight-length relationship of the alien northern brown shrimp Penaeus aztecus from the Central Aegean Sea is given at the end.